STUDIES ON A SARCOSINE OXIDASE OF BACTERIAL ORIGIN - Kopper, Paul H. (The Rockefeller University Press, 1950)
A "sarcosine oxidase" was prepared from a creatinine-decomposing strain of Pseudomonas aeruginosa. The enzyme is inactivated by drying, lyophilization, and dialysis against distilled water. No dialyzable cofactor was found. Optimal activity of the enzyme is reached at pH 7.8. Enzyme activity is directly proportional to enzyme concentration and also to substrate concentration up to the point of saturation of enzyme with substrate molecules. One molecule of enzyme combines with one molecule of substrate. Data concerning the effect of temperature and of a variety of chemical compounds on the enzyme are presented. Its inactivation by heat follows the course of a first order reaction, and the critical thermal increment between 48° and 52°C. was calculated to be 103,000 calories per mol. The relationship of enzyme concentration to heat inactivation rates is illustrated.